FACTORS AFFECTING EMPLOYEE PERFORMANCE IN EAST LUWU REGENCY: WORK MOTIVATION AND JOB TRAINING, THROUGH ORGANIZATIONAL COMMITMENT - Riyadi Para'pak; Suhardi M. Anwar; Ilham Tahier; Hadi Pajarianto, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Employee performance is an important issue in all organizations, both government and private, because it can have implications for the overall performance of the organization. Employees who are not professional in their work will bring multi-effects, as a result vital sectors will be hampered. This study aims to explore how employees perform by including work motivation and job training variables, as well as organizational commitment as mediation variables. The research method uses a quantitative research design with a survey research approach using 5 liker scales (agree – disagree) and distribute questionnaires to 60 respondents who are employees in related agencies. The data analysis used in this study is Descriptive Statistics, Validity and Reliability Test of SEM Model. The results of the study showed that the variable of job training on organizational commitment had a positive or significant influence as well as the variable of organizational commitment to performance. Meanwhile, some variables have negative or insignificant results.